Sources of inflation and output fluctuations in Poland and Hungary: Implications for full membership in the European Union - Selahattin Dibooglu; Ali M. Kutan (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2001)
This paper examines the sources of fluctuations in inflation and output in two leading transitioneconomy candidates for admission to the European Union (EU), Poland and Hungary. Using a rational expectations, dynamic open economy aggregate supply- aggregate demand model, we consider real oil price, supply, balance of payments, demand, and monetary disturbances incorporating important features of transition economies such as balance of payments disturbances and finite capital mobility. Evidence indicates that supply shocks explain a sizable portion of price level movements in Hungary while demand shocks are dominant in price level movements in Poland. Monetary shocks are an important source of output fluctuations in the short run in Hungary suggesting nominal inertia. In Poland, real demand shocks affect output in the short run (up to one year), while monetary shocks are negligible. Estimates of “core inflation” based on historical realizations of the shocks suggest that a major component of inflation has been demand driven, “core” inflation. Finally, policy implications of these findings regarding EU membership are evaluated.
Keywords: E3; P2; O5; C5; 330; Business Cycles; Inflation; Transition Economies; Time Series Models; Inflation; Konjunktur; Schock; Übergangswirtschaft; Schätzung; VAR-Modell; U